A Case for Creative Misunderstanding - Mazer, S (Te Ara Poutama, AUT University, 2015)
The differences between us necessitate the dialogue, rather than disallow it – a dialogue must take place, precisely because we don’t speak the same language. (Ahmed, 2000, p. 180, italics in the original) Human ways of life increasingly influence, dominate, parody, translate, and subvert one another. (Clifford, 1986, p. 22) I begin with an admission: I’m not Māori, not indigenous in any place or in any way that would allow me to speak and write with such authority. Nor, for that matter, am I a dancer. I’m an American theatre-trained, performance ethnographer. As a performance ethnographer, everywhere I go, everywhere I look, I see performances, and while I may not understand the language or conventions of the performances I see, even so I tell the story of my seeing performances to others.